Training model for lower level operational workers (wage-earners) in local authorities within the greater Western Cape metropolitan area - Kotze, Eugene Martin (Stellenbosch : Stellenbosch University, 2012)
Thesis (M.P.A.) -- University of Stellenbosch, 1995.